Growth performance of Boer goat in relation to sex and type of birth at the Goat Research Station in Nepal - Kadel, R; Malla, S; Ghimire, SH; KC, BB; Shrestha, PB (Bangladesh Journal of Animal Science, 2021)
This study was carried out at Goat Research Station, Bandipur, Tanahun, Nepal to evaluate the different factors affecting the growth performance of pure Boer goat since its arrival on 2015. A total of 225 kids of Boer goat born from 218 kidding does recorded between 2015 and 2019 were used for analysis of birth weight, weaning weight, eight month weight and yearling weight in response to sex and type of birth. The overall least square means for birth weight is 3.246 ± 0.056 kg, weaning weight is 17.86 ± 0.105 kg, eight month weight is 28.66 ± 0.2.6 kg and yearling weight is 45.10 ± 0.218 kg. The least square means across sex for birth weight, weaning weight, eight month weight and yearling weight were 3.368 ± 0.090 kg, 18.42 ± 0.226 kg, 31.69 ± 0.415 kg and 49.29 ± 0.707 kg for male and 3.136 ± 0.068 kg, 17.43 ±0.150 kg, 26.35 ± 0.378 kg and 42.18 ± 0.778 kg for female respectively. Sex and type of birth have significant effect on birth weight and weaning weight, while for eight month weight and yearling weight, sex have significant effect but no significant effect on type of birth. In conclusion, the overall growth performance of Boer goat in Goat Research Station was to the expectation and may increase on improvement of management and environmental effects. Bang. J. Anim. Sci. 2020. 49 (2): 166-169